In vitro human cord blood platelet lysate characterisation with potential application in wound healing. Issue 1 (30th October 2019) - Losi, Paola; Barsotti, Maria C.; Foffa, Ilenia; Buscemi, Marianna; De Almeida, Carolina V.; Fabbri, Marco; Gabbriellini, Sabrina; Nocchi, Francesca; Ursino, Silvia; Urciuoli, Patrizia; Mazzoni, Alessandro; Soldani, Giorgio
Abstract: Platelets contain abundant growth factors and cytokines that have a positive influence on the migration and proliferation of different cell types by modulating its physiopathological processes. As it is known that human umbilical cord blood platelet lysate (UCB‐PL) contains a supraphysiological concentration of growth factors, in the present study, we investigated its effectiveness in wound‐healing processes. Human UCB‐PL was obtained by the freeze/thaw of platelet concentrate (1.1 × 10 9 platelets/L), and its effect was evaluated on human or mouse endothelial cells, monocytes, fibroblasts, and keratinocytes in different concentrations. Human UCB‐PL was observed to have high levels of pro‐angiogenic growth factor than peripheral blood platelet‐rich plasma. Among the cell lines, different concentrations of human UCB‐PL were necessary to influence their viability and proliferation. For L929 cells, 5% of total volume was necessary, while for human umbilical vein endothelial cell, it was 10%. Cell migration on monocytes was increased with respect to the positive control, and scratch closure on keratinocytes was increased with respect to serum‐free medium with only 10% of human UCB‐PL. We concluded that the human UCB‐PL may be useful to produce a large amount of standard platelet concentrates sufficient for several clinical‐scale expansions avoiding inter‐individual variability, which can also be used as a functional tool for clinical regenerative application for wound healing.